2022
DOI: 10.3389/fgene.2022.902718
|View full text |Cite
|
Sign up to set email alerts
|

Good Cop, Bad Cop: The Different Roles of SRPKs

Abstract: SR Protein Kinases (SRPKs), discovered approximately 30 years ago, are widely known as splice factor kinases due to their decisive involvement in the regulation of various steps of mRNA splicing. However, they were also shown to regulate diverse cellular activities by phosphorylation of serine residues residing in serine-arginine/arginine-serine dipeptide motifs. Over the last decade, SRPK1 has been reported as both tumor suppressor and promoter, depending on the cellular context and has been implicated in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…This finding supports the evidence that the increased malignant potential of melanoma cells, along with the consequent worsening in patient prognosis, should also be related to SRPK2 activity. Although the best-known function of SRPKs is classically related to regulation of pre-mRNA splicing (Wang et al, 1998), new findings have shown that these kinases can act broadly, depending on their expression levels and subcellular localization, the signaling pathways in which they are involved, and according to the cellular state (Nikolakaki et al, 2022). Here, we showed that genetic targeting of SRPK2 affected actin filament polymerization by decreasing the formation of F-actin in B16F10 cells.…”
Section: Discussionmentioning
confidence: 71%
“…This finding supports the evidence that the increased malignant potential of melanoma cells, along with the consequent worsening in patient prognosis, should also be related to SRPK2 activity. Although the best-known function of SRPKs is classically related to regulation of pre-mRNA splicing (Wang et al, 1998), new findings have shown that these kinases can act broadly, depending on their expression levels and subcellular localization, the signaling pathways in which they are involved, and according to the cellular state (Nikolakaki et al, 2022). Here, we showed that genetic targeting of SRPK2 affected actin filament polymerization by decreasing the formation of F-actin in B16F10 cells.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, Srpk3 overexpression in mice results in cardiomyopathy 16 , not seen in the KO model. Like RBM20, SRPKs exhibit strong spatiotemporal expression profiles 13 16 , and their subcellular localization is regulated by their own phosphorylation 53 and acetylation 54 , suggesting that these kinases are involved in tightly controlled and fine-tuned pathways at different developmental stages and in response to external signals 17 , 55 . While their role in mRNA regulation is well studied 13 , it has recently been shown that SRPKs are also involved in ubiquitin signaling 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Candidate kinases include those belonging to the SRPK family of kinases, which target serine residues which lie in SR motifs (88), and this will be interesting to investigate especially as to date these kinases have not been linked to maintenance of genome stability. Intriguingly, enrichment of non-overlapping phospho-motifs specific to each individual inhibitor was observed: YX[pS/pT] for berzosertib and pSXXXTP YXS/T for gartisertib.…”
Section: Discussionmentioning
confidence: 99%